Transformative Leadership of School Principals in Improving the Quality of Education from an Islamic Perspective - Muhammad Ridho Fatkhul Humam; Mulya Putra; Aziz, Mahbub Humaidi; Bima Fandi Asy’arie (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to identify the application, components of the transformational leadership style, and analyze how this leadership style is applied in an Islamic perspective. This research is field research, where the type used is multisite using a qualitative approach. This research focuses on the Humanities Vocational School and At-Tayyibah Middle School, Kerinci Regency, Jambi Province. The findings of the discussion in this article, First. Implementation of TL in Humanities Vocational Schools to increase commitment and performance. Where, the role of the school principal is to maintain a harmonious work atmosphere and provide continuous moral support, to increase loyalty and work morale. Then, the principal also increases learning innovation and includes space for participation in decision-making. On the other hand, implementing TL at At-Tayyibah Middle School increases commitment and performance. Where the efforts made by the school principal are to have a strong sense of empathy towards the school community. Apart from that, the principal provides space for all school members to make decisions and can provide maximum performance. Second, the transformational leadership component is proven by the presence of a charismatic, firm, polite, courteous attitude, able to solve various problems, and trying to form superior students who can realize school goals under the desired achievements. Third, transformative leadership in an Islamic perspective includes providing the concept of deliberation in Islam called (shura); providing an attitude of justice and empowering equality among the school community; creating individual development and encouraging innovation under Islamic principles; and Providing moral and spiritual support to all school members.